Features of planning and landscaping of therapeutic landscapes for children’s hospitals - Kosyk, Oksana; Bilonog, Mariia (Theory and practice of design, 2022)
This article is devoted to the study of the health effects of nature on humans to create functional and aesthetically attractive green areas of children’s hospitals. The paper considers the basic principles of landscaping children’s hospitals, analyzes the world experience in landscaping children’s medical institutions, clarifies the role of the therapeutic landscape as the most functionally effective option for zoning green spaces in children’s hospitals. For efficient use of space near children’s hospitals landscape designers should provide areas for active and quiet recreation, as well as a separate garden for staff. A retreat garden and an activity garden usually have a similar layout, but a completely different atmosphere and landscaping approach. In the activity garden, visitors tend to ignore the landscaping techniques and focus on playgrounds and space components used in therapy. The main function of landscaping a garden for quiet relaxation is to create an atmosphere of privacy for solitude and balancing, to distract from negative emotions. Forming a functional green space near hospitals, the basic principles of the therapeutic landscape should be observed: visual and physical accessibility of green areas; inclusiveness; a variety of functional spaces that meet different needs; providing sensory stimulation. This will lead to a reduction in stress and ultimately ensure a quick recovery of patients. Proper functionally effective zoning of children’s hospital green spaces will contribute to the harmonious mental and physical development of children.